Treatment of relapsed acute promyelocytic leukemia - Lengfelder, Eva; Gnad-Vogt, Ulrike; Büchner, T.; Hehlmann, Rüdiger (Onkologie, 2003)
By all-trans retinoic acid (ATRA) and chemotherapy over 70% of patients with newly diagnosed acute promyelocytic leukemia (APL) may be cured; 20-30% of patients still relapse and require salvage therapy. For relapsed or refractory APL, a standard treatment has not yet been defined. However, several effective drugs and approaches have been described. Treatment options for relapsed APL include chemotherapy regimens used in the treatment of relapsed acute myeloid leukemia usually combined with ATRA or of other differentiating agents such as liposomal ATRA or synthetic retinoids. Presently, allogeneic peripheral stem cell or bone marrow transplantation is the treatment of choice for younger patients who have a histocompatible donor, as it gives the chance of cure in second or further relapse. For patients without a donor or for those who are not suitable for allogeneic transplantation, autologous stem cell or bone marrow transplantation may offer at least the possibility of a prolongation of remission, if the harvested cells are negative in the RT-PCR of PML/RARα. Arsenic compounds have a high antileukemic effectiveness on APL cells. Arsenic trioxide has recently been approved for relapsed or refractory APL. With this drug, complete hematologic remission rates of 80-92% and long-lasting molecular remissions were achieved in relapsed patients. For patients who do not qualify for these treatment options, monoclonal anti-CD33 antibodies may represent further treatment options.
Gesehen am 13.05.2022